Effect of Poxvirus Infection on Host Cell Deoxyribonucleic Acid Synthesis - Jungwirth, C. (1968)
Deoxyribonucleic acid (DNA) synthesis was studied in poxvirus-infected cells by measuring (14)C-thymidine incorporation into viral and host cell DNA. A complete separation of the two species of DNA was achieved by combining the previously used “Dounce method” with a separation method based on different reannealing properties of viral and vertebrate DNA. Shortly after infection of HeLa cells with poxviruses, a burst of viral DNA synthesis occurred in the cytoplasm, but a rapid inhibition of host-cell DNA synthesis in the nucleus was observed. This inhibition of cellular DNA synthesis was also found if an accumulation of viral DNA was prevented. At high multiplicites, ultraviolet-irradiated virus inhibited host-cell DNA synthesis to the same extent as fully infectious poxvirus. Under the same conditions, heating at 60 C for 15 min caused a decrease in the ability of cowpox virus to inhibit host-cell DNA synthesis, but did not produce the same effect on vaccinia virus strain WR.